What is the impact of comorbid depression on adolescent substance abuse treatment? - Hersh, Jacqueline; Curry, John F; Kaminer, Yifrah (Substance abuse, 2014)
Substance use disorders (SUDs) are among the most common psychiatric diagnoses in adolescents. Some research suggests that comorbid depression in adolescents with SUD is associated with increased likelihood of alcohol dependence, poorer social competence, and greater risk for suicide attempts. However, little is known about how depression influences adolescent substance abuse treatment retention and outcomes. This review aimed to summarize the effects of comorbid depression on treatment retention and outcomes across 13 adolescent SUD treatment studies. RESULTS indicated that depression has a mixed relationship with treatment retention and outcomes, exerting a negative, positive, or nonsignificant effect depending on aspects of the study. More research needs to be done, particularly addressing the potential mediators and moderators of the relationship between depression and SUD outcomes. Importantly, recognizing that the studies varied widely in hypotheses and research methods, the field needs to develop more standardized methods to allow for a clearer understanding of the role of comorbid depression.